Strategies of Cultural Gap Translation in World Herritage – Sites and Living Culture of Indonesia - M. Agus Suriadi (Buletin Al-Turas, 2015)
AbstractTranslating certain texts from one language to another language might become one of the most challenging tasks for a translator, especially for a text containing a lot of cultural words. A translator is frequently faced with the problem of how to treat the implicit aspects of culture and how to find appropriate strategies in translating a text from a Source Text (ST) into Target Text (TT). It is probably right to say that a translator has to deal with a lot of thigs to do which have not, perhaps, been aware for cultural gaps and their significance in translation. Many translation theorists have concerned with the problems of cultural knowledge and cultural differences for many decades, might be, since translation as sciences had been recognized. Cultural knowledge and cultural differences begin to draw attention from many experts to focus on translation theories and to conduct translation training for academic studies. Therefore, the present paper aims at presenting strategies of translating the cultural concepts by different theorists. In addition to this, it is also expected to reinforce a translator to choose the appropriate procedures and strategies in translating process.---AbstrakMenerjemahkan teks-teks tertentu dari suatu Bahasa ke Bahasa yang lain, seringkali, menjadi salah satu tugas berat sekaligus merepotkan bagi seorang penerjemah, khusunya dalam menerjemahkan teks-teks yang mengandung banyak kata-kata budaya. Seorang penerjemah sering kali dihadapkan pada masalah-masalah bagaimana mengaplikasikan aspek-aspek budaya dan bagaimana menemukan strategi dalam menerjemahkan sebuah teks dari Bahasa Sumber (BSu) ke dalam Bahasa Sasaran (BSa). Hal ini, mungkin saja, dikarenakan seorang penerjemah harus direpotkan dengan hal-hal, yang bisa jadi, seringkali tidak disadari oleh seorang penerjemah dalam menghadapi perbedaan budaya yang memiliki peran penting dalam penerjemahan.Banyak pakar teori penerjemahan merasa prihatin dengan masalah-masalah yang berkenaan dengan perbedaan dan pemahaman budaya dalam kurun waktu yang cukup lama, yang kemungkinan besar, telah ada sejak penerjemahan dijadikan sebagai disiplin ilmu pengetahuan. Perbedaan dan pengetahuan budaya ini kemudian menyita perhatian dari para pemerhati penerjemahan untuk menyoroti masalah teori penerjemahan dalam kajian akademis. Oleh karena itu, tulisan ini bertujuan untuk membahas masalah strategi dalam menerjemahkan konsep-konsep budaya dengan mengacu pada pendapat pakar penerjemahan tertentu, seperti Peter Newmark. Di samping itu, tulisan ini juga diharapkan dapat membantu penerjemah untuk memilih strategi yang cocok dalam melakukan proses penerjemahan.